Doğankuzu ve Mortaş boksit cevherlerinin liç şartlarının incelenmesi - Canözer, İlker (Fen Bilimleri Enstitüsü, 1997)
Yapılan deneylerle böhmitik karakterdeki Doğankuzu ve Mortaş boksit cevherlerinin liç şartlan incelenmiştir. Elde edilen sonuçlara göre, her iki cevher için de en iyi kostik modül oranının 3.5 ve en iyi K/S oranının ise 1/5 olduğu belirlenmiştir. Bununla beraber, hem Doğankuzu ve hem de Mortaş cevheri için en uygun tane boyutunun (-53) um olduğu saptanmıştır. Ayrıca yapılan deneylerle 225°C'ye kadar olan sıcaklıklarda ve kısa çözümlendirme sürelerinde Mortaş cevheri ile, Doğankuzu cevherine oranla daha iyi bir liç verimine ulaşılmıştır. Fakat bu sıcaklıklarda, çözümlendirme süresi arttıkça bu durum Doğankuzu cevheri lehine gelişim göstermektedir. 240 °C'de ise, çok kısa çözümlendirme sürelerinde bile (ör: 15 dak.) Doğankuzu cevheri ile yüksek liç verimlerine (% 80.13) ulaşılmıştır, l saatlik çözümlendirme süresinde ise liç veriminin % 99.95 olduğu saptanmıştır. Oysa Mortaş cevheri ile buna yakın bir orana ulaşmak (% 97.22) yaklaşık olarak 3 saat almaktadır. Bunun yanısıra, çözeltilerdeki SiOa konsantrasyonları da incelenmiş ve cevherlerin hangi oranda reaktif silika içerdikleri belirlenmiştir. Daha yüksek SİÛ2 oranına sahip olan Mortaş cevherinde reaktif silika içeriği, Doğankuzu cevherinin reaktif silika içeriğinden daha düşük çıkmıştır. Kısa sürelerde Mortaş cevherinin daha iyi bir liç verimi alınmasının nedeni,bu düşük reaktif silika içeriği olabilir. Bunun yanısıra Mortaş cevherinin içerdiği a - kuartz miktarının Doğankuzu cevherindekinden daha düşük olması da bunda etken rol oynamış olabilir. En son aşamada ise, Crank - Ginstling - Brounstein metodu kullanılarak, her iki cevher için de kinetik model araştırması yapılmıştır. Bu çalışmaya göre, her iki cevher de topokimyasal olarak çözünmekte ve difüzyon kontrollü mekanizmaya uymaktadırlar.

Dtuılln Ptrt m«l*(lıl> l FfeptfBtlon j CaO r~* *.«j Dlgetllon -^^ IIIHM9I l- S'»*'" J llquo< l Ut.U.,8 J l FUıttlng l !_. J l . l w«ı«t / \ , i, l N»OH l(jquor j j S^trf L__-J Saod l l Suıg* l l S8p»r«llon l L i W»»hlng l, ry--*f ^-"^ t^r^v. l«,puH*y 1,"".,."",, l l Mn. n.,Wu, l l H,.MU? l Rarnoval l J | Sapanllon l.-| W»thlna j \ /-T--'. f Sl*»m J l IWpuıUI«« H«»llnB ^ l Cool'ng l r^j L-^^ | PttclpUallon *^ t. l t9-" I CUıılflollon l . ı r H~ L Watar R«Wut w"hl"fl f* j r.ı.ro.» j 1 ' ru«ı l l »l C»ltln»Ilon l Alt°3 ^ Figüre 1. Bayer Process Flowsheet XII 3. BAYER PROCESS Bayer process consist 3 stages: a) Digestion of the bauxite ores with NaOH solution. b) Seperation Solid / Liqour and settling of the red mud. c) Precipitation of Al(OH)? by seeding and calcination. The Bayer process flovvsheet are given figüre l. The aim of this process is to produce alumina vvhich is economically and have high - quality.the most important step of the process is the digestion of the bauxite öre. 4. DİGESTİON Aluminium - hydroksid minerals react with NaOH at high temperature and high pressure and move into the liquor. Gibbsitic ores are digested with 120 - 140 g Na2O /1 at 120 - 150 °C.. Required temperature and konsantration for digestion of boehmitic and diasporic ores are 180 - 220 °C and 180 - 250 g Na20 /1. Gibbsite :.> ı f iri °r (A12O3. 3 H20)k + 2(NaOH)ç ) |NaAl(OH)4|ç Boehmite : >,'>nn°p (A1203. H20)k + 2(NaOH)ç +2 H20 >2W L ) 2|Na A1(OH)4 |ç Diasporite: (A1203. H20)k + 2(NaOH) +Ca(OH)2 + 2 H20 > 2|Na A1(OH)4| + Ca(OH)2 XI Dtuılln Ptrt m«l*(lıl> l FfeptfBtlon j CaO r~* *.«j Dlgetllon -^^ IIIHM9I l- S'»*'" J llquo< l Ut.U.,8 J l FUıttlng l !_. J l . l w«ı«t / \ , i, l N»OH l(jquor j j S^trf L__-J Saod l l Suıg* l l S8p»r«llon l L i W»»hlng l, ry--*f ^-"^ t^r^v. l«,puH*y 1,"".,."",, l l Mn. n.,Wu, l l H,.MU? l Rarnoval l J | Sapanllon l.-| W»thlna j \ /-T--'. f Sl*»m J l IWpuıUI«« H«»llnB ^ l Cool'ng l r^j L-^^ | PttclpUallon *^ t. l t9-" I CUıılflollon l . ı r H~ L Watar R«Wut w"hl"fl f* j r.ı.ro.» j 1 ' ru«ı l l »l C»ltln»Ilon l Alt°3 ^ Figüre 1. Bayer Process Flowsheet XII 5. LEACHING EXPERIMENTS The leaching conditions for Doğankuzu and Mortaş boehmitic bauxite ores were investigated by these experiments. The experiments consist the following stages: a) Investigation for effect of the grain - size on the leaching efficiency. b) Investigation for effect of the temperature on the leaching efficiency. c) Investigation for effect of the digestion time on the leaching efficiency. d) Investigation for effect of the caustic ratio on the leaching efficiency. e) Investigation for effect of the Solid / Liquor ratio on the leaching efficiency. f) Investigation for the behaviour of SİÛ2 during the digestion. 6. RESULTS OF THE EXPERIMENTS Caustic modüle which provide the best leaching efficiency for Doğankuzu and Mortaş bauxites were 3.5. and the favour Solid / Liquor ratio noticed by the experiments were 1/5. However, it found that the the best grain - size were (-53 um) for either Doğankuzu ör Mortaş ores. At the temperature until 225 °C and the short digestion times, the betler leaching efficiency were erreiched by the digestion of Mortaş bauxite than that of the digestion of Doğankuzu bauxite. But at these temperature, when the digestion time \vere increased, the leaching efficiency by the digestion Doğankuzu bauxite developed. At 240 °C, at even very short digestion times (for ex: 15 min.) the high leaching efficiency (% 80.13) were erreiched. When the chosen digestion time were l hour, the leaching efficiency were arised (% 99.95). But, by the digestion of Mortaş bauxite, 3 hours were necessary for XIII this efficiency. However, the Si02 konsantration of the liquors were searched and the reactif silica contents of them were determined. The reactif silica content of Mortaş ore which have higher SİO2 amounts than Doğankuzu ore were found lower than that of Doğankuzu ore. At short times, the reason of better efficiency from the Mortaş ore could be lower silica content. However, a - quartz content of Mortaş bauxite were lower than that of Doğankuzu bauxite, too. One of the other reason for better efficiency could be that. At the final stage, the kinetics for both of the ores were investigated by applying the method of Crank - Ginstling - Brounstein. İn order to this investigation, both of these ores were agree with the shrinkage - core model and the mechanism of diffusion control. XIV
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Boksit; Liçing; Bouxite; Leaching